Chain saws Part 7. Method of evaluating engine performance including fuel consumption (BSI, 1988)
Sawing machines, Chain saws, Portable machine tools, Machine tools, Internal combustion engines, Forestry equipment, Prime movers, Fuel consumption, Performance testing, Testing conditions